Buying and Selling iPhones with Illegal IMEI Without Warranty in the Perspective of DSN Fatwa No. 146/DSN-MUU/XII/2021 on Sharia-Based Online Stores (Case Study on Facebook Marketplace) - Sahliah; Triana (Journal Equity of Law and Governance, 2024)
This research analyzes the practice of buying and selling iPhones with illegal IMEI codes without warranty through the lens of Fatwa DSN No: 146/DSN-MUU/XII/2021, which addresses online stores based on Islamic principles. Employing a qualitative approach, the study focuses on case studies from the Facebook marketplace. Data is collected through the observation of transactions involving illegal iPhones on the platform and an analysis of the relevant Fatwa DSN. Findings indicate that these transactions violate Islamic principles, specifically gharar (uncertainty) and fraud. The study highlights the implications of these practices on public welfare and justice, underscoring the need to enforce Islamic law in online business contexts. This research contributes to the understanding of Islamic business ethics and the necessity for stricter regulations to uphold justice and public welfare in online transactions. Ensuring legal and transactional validity, promoting public welfare, and maintaining social justice are essential for conducting Sharia-compliant and fair transactions in the digital marketplace.